The impact of domestic rainwater harvesting systems in storm water runoff mitigation at the urban block scale. (15th April 2017) - Palla, A.; Gnecco, I.; La Barbera, P.
Abstract: In the framework of storm water management, Domestic Rainwater Harvesting (DRWH) systems are recently recognized as source control solutions according to LID principles. In order to assess the impact of these systems in storm water runoff control, a simple methodological approach is proposed. The hydrologic-hydraulic modelling is undertaken using EPA SWMM; the DRWH is implemented in the model by using a storage unit linked to the building water supply system and to the drainage network. The proposed methodology has been implemented for a residential urban block located in Genoa (Italy). Continuous simulations are performed by using the high-resolution rainfall data series for the ''do nothing'' and DRWH scenarios. The latter includes the installation of a DRWH system for each building of the urban block. Referring to the test site, the peak and volume reduction rate evaluated for the 2125 rainfall events are respectively equal to 33 and 26 percent, on average (with maximum values of 65 percent for peak and 51 percent for volume). In general, the adopted methodology indicates that the hydrologic performance of the storm water drainage network equipped with DRWH systems is noticeable even for the design storm event (T = 10 years) and the rainfall depth seems to affect the hydrologic performance at least when the total depth exceeds 20 mm. Graphical abstract: Highlights: Domestic Rainwater Harvesting (DRWH) systems control storm water runoff. Continuous simulations are performed at least at the urban block scale. Modelling results confirm the impact of DRWH systems on runoff mitigation. Hydrologic performance are evaluated on event basis and statistically examined. The rainfall depth higher than 20 mm affects the hydrologic performance.